Analysis of The Influence of Financial Literacy and Locus of Control Mediated by Risk Perception on Investment Decisions - Maharani, Ayu; Moh. Athoillah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Technological advancements in the era of globalization have made information more accessible and broadened public knowledge. Individuals need adequate financial skills and knowledge to make informed decisions, maximize wealth, and improve personal and family well-being. Investing is an effective approach to financial management. Although interest in capital market investment is increasing, especially among young investors, there are obstacles such as lack of understanding, financial constraints, psychological factors, and concerns about risk. This study aims to analyze financial literacy, locus of control, and risk perception in relation to investment decisions among Generation Z, using quantitative methods and PLS-SEM analysis. The results indicate that these three factors positively influence investment decisions. The implications of this research include the need for improved financial literacy to make better investment decisions. Financial institutions and governments are encouraged to collaborate to enhance financial education and develop financial products for the public.